Comparative methods of repairing left ventricular aneurysms. - Türkay, C (1997)
Between 1 March 1992 and 31 June 1996, we enrolled 72 patients with left ventricular aneurysms in a prospective, nonrandomized study to compare--by study of cardiac indices, single-plane ejection fractions, and nuclear ventriculograms--the effects of classical aneurysmectomy (group 1, n = 36) with those of endoaneurysmorrhaphy (group 2, n = 36). Preoperative and postoperative cardiac index measurements were, respectively, 1.96 +/- 0.6 and 3.51 +/- 0.53 for group 1, and 1.96 +/- 0.31 and 3.43 +/- 0.41 for group 2. In this regard, there was not any significant difference between the groups preoperatively or postoperatively. Preoperative and postoperative multiple-gated acquisition measurements, were, respectively, 34.3 +/- 7.76 and 43.1 +/- 11.1 for group 1, and 37 +/- 3.88 and 66.5 +/- 5.2 for group 2. Although there was not any significant preoperative difference between the groups (P = 0.34), group 2 had significant postoperative improvement in left ventricular ejection fractions (P < 0.001). Preoperative and postoperative single-plane contrast ventriculographic ejection fractions were, respectively, 43.4 +/- 8.7 and 48.6 +/- 11.2 for group 1, and 43.8 +/- 5.5 and 60.8 +/- 15.1 for group 2. Again, there was not any significant difference between the 2 groups in preoperative left ventricular ejection fractions (P = 0.87), but the postoperative left ventricular ejection fractions of group 2 were significantly better than those of group 1 (P = 0.022). We conclude that left ventricular functional improvement with endoaneurysmorrhaphy is superior to that with classical aneurysmectomy.